Impurity-Driven Phase Behaviour Changes and Risk of Phase Separation in CO₂ Transport and Storage - Patel, Anshurani; Chaturvedi, Anjna; Siddiqui, Naved; kumhar, Dinesh; Mishra, Rajeev Kumar; Kesharwani, Shivangi (Journal of Neonatal Surgery, 2025)
The integration of carbon capture and storage (CCS) into climate mitigation strategies demands a comprehensive understanding of the phase behaviour of CO₂, especially when transported and injected with impurities. Industrial CO₂ streams are rarely pure and typically contain varying amounts of gases such as nitrogen (N₂), methane (CH₄), oxygen (O₂), sulphur dioxide (SO₂), hydrogen sulphide (H₂S), argon (Ar), and water vapor (H₂O). These impurities significantly alter the thermophysical properties and phase behaviour of CO₂, affecting its compressibility, viscosity, density, and critical point. Impurities can shift the phase envelope, increase the risk of two-phase flow, and cause phase separation during transport and injection, potentially leading to operational inefficiencies, increased corrosion risk, and mechanical stress on infrastructure. This review critically analyses how different impurities influence CO₂ phase behaviour under pipeline and reservoir conditions. Emphasis is placed on the implications of phase instability for flow assurance, pipeline integrity, and reservoir performance. Additionally, we discuss current modelling approaches and experimental findings that aid in predicting and managing impurity-driven phase transitions. Understanding these effects is essential for designing safe and efficient CCS systems, especially under high-pressure, high-temperature subsurface conditions.